Mechanical response of flexible pavements enhanced with geogrid-reinforced asphalt overlays. Issue 3 (9th December 2015) - Correia, N. S.; Zornberg, J. G.
Abstract : The use of geosynthetic reinforcements placed underneath asphalt overlays, which has been typically used to minimise problems associated with reflective cracking, is evaluated in this study as an approach to improve pavement structural capacity. Whereas geosynthetics have been used to increase the pavement structural performance when used to reinforce the base aggregate, as reported in numerous laboratory and evaluations experiments, such improvement has not been evaluated for the case of geosynthetics within asphalt layers. Accordingly, this paper presents the results of large model tests involving both reinforced and unreinforced hot mix asphalt overlays. Cyclic wheel loads were applied using an accelerated pavement test facility that was specifically developed for this research. A number of pavement sections were constructed using a polyvinyl alcohol geogrid as reinforcement inclusions. The results show a considerable increase in pavements structural performance, as quantified by reduction of strains in the asphalt concrete layers, in the vertical stresses within the pavement layers and in the resilient displacements at the wearing surface. The use of geogrid reinforcements was also found to lead to reduce rutting and permanent lateral movements in the surface layer. Overall, the use of geogrids within asphalt overlays was found to act as a reinforcement element that provide enhanced structural capacity to flexible pavements.